Sustaining Traditional Textile Businesses: How Creative Economy Supports Sasirangan MSME in Banjarmasin - Hikmahwati Hikmahwati; Nurul Mukhlisah (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
This study analyzes the effect of creative economy development on the business sustainability of Sasirangan MSMEs in Banjarmasin City. Sasirangan fabric is a cultural heritage closely associated with the local community and plays a strategic role in supporting the regional economy. This research employs an associative quantitative approach using simple linear regression analysis to examine the relationship between variables. The research variables include creative economy development and the sustainability of Sasirangan MSMEs. The results indicate that creative economy development has a significant effect on the sustainability of Sasirangan MSMEs in Banjarmasin City, although its contribution remains relatively limited, as reflected by a coefficient of determination of 11.4%. These findings suggest that strengthening the creative economy contributes to sustaining Sasirangan MSMEs; however, additional supporting factors are required to enhance its overall impact.